Application of character card learning media to improve character appreciation in theater art learning in Grade XI-3 SMAN 9 Malang - Ahmad Sholikin (Humanities Horizon, 2026)
This research aims to increase students' involvement and understanding in the subject of Arts and Culture, especially in contemporary theater materials, through the use of Character Card learning media. The background of this research arises from the low level of understanding of grade XI 3 students at SMAN 9 Malang on the basics of role-playing, especially in the aspect of deepening character characters, which is caused by the lack of innovation and the limitations of media in the learning process. The method used is Class Action Research (PTK), which is carried out in two cycles with stages of planning, implementation, observation, and reflection. Data collection is carried out through observation, learning outcome tests, and documentation. The results showed a significant increase in student participation and understanding after the implementation of the action. The participation rate of students increased from 58% in the first cycle to 83% in the second cycle. Media Character Cards have proven to be effective in creating a more interactive, fun, and meaningful learning atmosphere.